Polska bibliografia wyborczo-referendalna za 2017 rok: https://doi.org/10.26485/SW/2018/26/6 - Frydrych-Depka, Anna; Raźny, Paweł (Studia Wyborcze, 2018)
Polska bibliografia wyborczo-referendalna za 2017 rok